POPULATION STRUCTURE OF Cerithidea obtusa (GASTROPODA) IN THE INTERTIDAL ZONE OF THE EASTERN COAST BENGKALIS ISLAND RIAU PROVINCE - Fitriani, Nely; Nasution, Syafruddin; Mulyadi, Aras (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
This research investigates the population dynamics of the gastropod Cerithidea obtusa along the eastern intertidal zones of Bengkalis Island, focusing on species abundance, spatial distribution, and size variation. Conducted over the span from December 2023 to January 2024, this investigation took place at two specific locales on the east coast of Bengkalis Island: Sekodi Village (Station I) and Teluk Lancar Village (Station II), employing a comprehensive survey methodology. The intertidal zones were segmented into upper, middle, and lower subzones, each with three transects containing one m² plot. Temperature, salinity, pH levels, substrate composition, and organic matter content were measured as indicators of the quality of the environment. The results revealed a significant difference in population density between the stations, with Station I showing the highest abundance at 240.000 ind/Ha and Station II the lowest at 33.300 ind/Ha. The middle subzone at Station I was the most populated, with 93.300 ind/ha. Shell size analysis revealed three categories: small (<3,35 mm), medium (3,35-4,05 mm), and large (≥4,05 mm), with medium-sized shells being the most prevalent. The distribution pattern of C. obtusa exhibited both uniform and clustered arrangements. A significant disparity in abundance was noted between Station I and Station II, with a p-value of 0,000, underscoring the considerable